Growth of a bonelike apatite on chitosan microparticles after a calcium silicate treatment - Leonor, I. B. (2008)
Bioactive chitosan microparticles can be prepared successfully by treating them with a calcium silicate solution and then subsequently soaking them in simulated body fluid (SBF). Such a combination enables the development of bioactive microparticles that can be used for several applications in the medical field, including injectable biomaterial systems and tissue engineering carrier systems. Chitosan microparticles, 0.6 lm in average size, were soaked either for 12 h in fresh calcium silicate solution (condition I) or for 1 h in calcium silicate solution that had been aged for 24 h before use (condition II). Afterwards, they were dried in air at 60 !C for 24 h. The samples were then soaked in SBF for 1, 3 and 7 days. After the condition I calcium silicate treatment and the subsequent soaking in SBF, the microparticles formed a dense apatite layer after only 7 days of immersion, which is believed to be due to the formation of silanol (Si– OH) groups effective for apatite formation. For condition II, the microparticles successfully formed an apatite layer on their surfaces in SBF within only 1 day of immersion.